Emotional availability in mother-child interaction: the effects of maternal depression in remission and additional history of childhood abuse - Kluczniok, Dorothea; Bödeker, Katja; Fuchs, Anna; Attar, Catherine Hindi; Fydrich, Thomas; Fuehrer, Daniel; Dittrich, Katja; Reck, Corinna; Winter, Sibylle; Heinz, Andreas; Herpertz, Sabine; Brunner, Romuald; et al. (Depression and anxiety, 2016)
Background The association between maternal depression and adverse outcomes in children is well established. Similar links have been found for maternal childhood abuse. One proposed pathway of risk transmission is reduced maternal emotional availability. Our aim was to investigate whether sensitive parenting is impaired in mothers with depression in remission, and whether among these mothers childhood abuse has an additional impact. Methods The mother-child interaction of 188 dyads was assessed during a play situation using the Emotional Availability Scales, which measure the overall affective quality of the interaction: maternal sensitivity, structuring, nonhostility, and nonintrusiveness. Mothers with depression in remission were compared to healthy mothers. Children were between 5 and 12 years old. Group differences and impact of additional childhood abuse were analyzed by one-factorial analyses of covariance and planned contrasts. Results Mothers with depression in remission showed less emotional availability during mother-child interaction compared to healthy control mothers. Specifically, they were less sensitive and, at trend-level, less structuring and more hostile. Among these mothers, we found an additional effect of severe maternal childhood abuse on maternal sensitivity: Mothers with depression in remission and a history of severe childhood abuse were less sensitive than remitted mothers without childhood abuse. Conclusions Our data suggest that depression impacts on maternal emotional availability during remission, which might represent a trait characteristic of depression. Mothers with depression in remission and additional severe childhood abuse were particularly affected. These findings may contribute to the understanding of children's vulnerability to develop a depressive disorder themselves.